Marriage and cyber infidelity: repercussions and legal solutions - Mohamed, Duryana (Onikilevha Yayincilik A.S, 2019)
Problem statement: Marital infidelity has become one of the most traumatic life experiences in the society today. It is the greatest danger threatening family life and destroys marriages thus leading to increased divorce rates in the society. This is because it signals relationship problems between couples. Modern technology and social media provide increased possibilities for communication and relationships with others, thus, creating more avenues for individuals to be unfaithful to their partners. Although physical and emotional are often the most highly recognized forms of infidelity, cyber infidelity is becoming increasingly prevalent. This isi one of the effects caused by Internet technology. There are many literatures on the topic of cyber infidelity in the west, but not many have discussed the topic in the Malaysian context. The objective of this paper is to discuss the concept of cyber infidelity, its repercussions and possible legal solutions in curbing this intricate problem in the marriage institutions in Malaysia. It is also aimed to provide awareness to marriage couples on the importance of being faithful and the danger of Internet technology. The methodology adopted in this paper is based on the existing laws, analysis of law reports, case laws, leading textbooks and journal articles. Findings: The research shall provide recommendations and suggestions for improvement of the existing laws in curbing cyber infidelity which has affected the marriage institution. This cyber affair or cyber infidelity should be tackled by adopting certain regulations to control their sharing of secrets and personal information online. The act can be considered as misused of Internet facilities or violation of personal privacy. By referring to relevant cyber laws such as Communication and Multimedia Act 1998 (CMA) and other relevant laws perhaps the matter can be solved or reduced. The significance contribution of the study is that the findings may help to preserve the family institution as a whole.